An exploration of the (changing) roles, functions and challenges experienced by policewomen in the operational environment of the SAPS: Western Cape Province - Retief, Rita (Department of Public Law, 2026)
Scholarly interest in gender and policing has grown exponentially over the past two decades. This study is situated within that body of literature and explores the changingrole, functions and challenges experienced by policewomen appointed in the operational policing environment of the South African Police Service (SAPS). The intent is to develop insight into the first-hand experiences and perceptions of operational policewomen and to inform practice initiatives that accommodate the specific needs of policewomen entering the operational sphere of policing in the SAPS. The overall research question in this study is: How has operational policewomen experienced and perceived the challenges and barriers encountered in the execution of their respective policing roles in the masculine domain of operational policing in the SAPS over the last twenty years? The question is explored by focusing on police women in the province of the Western Cape. Exploratory-descriptive research was done by adopting a qualitative research design. A semi structured interview schedule was utilised for one-on-one interviews and one focus group session with a sample of fifteen experienced operational policewomen, with rank levels ranging from Major General to Lieutenant Colonel. The sample size although relatively small can be deemed representative of the whole as the number of commissioned operational policewomen in the Western Cape province is limited. Collected data was analysed by means of thematic analysis and presented as narratives focussing on four major themes. The conclusions drawn from the study indicate that the evolvement and broadened scope of policewomen in operational policing are achieved through personal efforts and determination despite challenges encountered in navigating career paths in policing. Although not well represented in all operational environments in the WC, policewomen are making valuable contributions. Not only do they add critical value in enhancing operational effectiveness but also contribute towards enhancing police legitimacy, regardless of their minority status within the police organisation.